Histamine in Inflammation - Thurmond, Robin L.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The year 2010 marks the centennial for the identification of histamine and the first glimpse of its many physiological functions. From these initial findings a rich tapestry of research has uncovered roles for histamine in almost every physiological process with new findings emerging every year. These diverse roles of histamine have made for fertile ground for the discovery of novel therapeutics, and these drugs have been so successful that the term (3z(Bantihistamine(3y (Bhas entered the common lexicon. This book is an attempt to give a snapshot in time as to the current understanding of the role of histamine in just one important therapeutic area$1 (Binflammation.s
One Hundred Years of Histamine Research -- Molecular Pharmacology of the Four Histamine Receptors -- Histamine Synthesis and Lessons Learned from Histidine Decarboxylase Deficient Mice -- Histamine in Allergic Rhinitis -- The Role of Histamine in Ocular Allergy -- The Role of Histamine in Asthma -- Antihistamines in the Treatment of Urticaria -- Histamine and Antihistamines in Atopic Dermatitis -- Histamine, Immune Cells and Autoimmunity -- Histamine in Neurotransmission and Brain Diseases -- Histamine in Normal and Malignant Cell Proliferation -- The Future Antihistamines: Histamine H3 and H4 Receptor Ligands.
Keywords: Medicine; Human physiology; Biomedicine; Biomedicine general; Human Physiology